PENGEMBANGAN APLIKASI WEB BASED DOCUMENTS SIMILARITY MEASURE MENGGUNAKAN MODEL RUANG VEKTOR PADA DOKUMEN BERBAHASA INDONESIA - Made Satria Wibawa (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
This study was aimed at: (1) designing the application of Interactive DistanceLearning based on web for the learning of HTML (Hypertext Markup Language), (2)implementing design the application of Interactive Distance Learning based on web forthe learning of HTML (Hypertext Markup Language). The learning of HTML(Hypertext Markup Language) have been developed becomes an interactive learning,and the communication able to happen among learners and between the tutor of HTMLit self.In designing and implementing the application design, the author used waterfallmethod which is usually called as classic life cycle model. This waterfall model is aclassic model which creates the software systematically and sequentially that includessome stages namely: (1) requirements definition, (2) system and software design, (3)implementation and unit testing, and (4) integration and system testing.The results of the analysis, the construction, the implementation and testing onthis study was the creation of an interactive application that support the HTML learnersto study the HTML learning without depend on direct meeting, that implemented byAdobe Dreamweaver CS3 and XAMPP version 1.7.1 . The implementation of thisapplication is high recommended run in Mozilla Firefox 11.0 and Google Chrome 19.0browser.